A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas - Alvarez, Fernando; Iliffe, Thomas M.; Villalobos, José Luis (Zootaxa, 2017)
A new species of mud shrimp of the genus Naushonia Kingsley, 1897 is described from two anchialine caves on the island of Great Abaco in the Bahamas. Naushonia tinkeri n. sp. is the fifteenth species in the genus and the second to be described from the Bahamas. The new species is morphologically similar to N. augudrea (Juarrero & García, 1997) from Holguín Province, eastern Cuba, with which it shares a carapace with cervical and cardiac grooves; however, it can be distinguished by having a pigmented cornea, the first pereiopod with a proportionately longer propodus and dactylus without a toothed external margin, and the telson longer relative to the uropod length. The new species inhabits anchialine caves and is the largest one reported until now.